Rapid molecular tests for detection of antimicrobial resistance determinants in Gram-negative organisms from positive blood cultures: a systematic review and meta-analysis. (March 2020) - De Angelis, G.; Grossi, A.; Menchinelli, G.; Boccia, S.; Sanguinetti, M.; Posteraro, B.
Abstract: Background: Timely detection of antimicrobial (cephalosporin/carbapenem) resistance (AMR) determinants is crucial to the clinical management of bloodstream infections caused by Gram-negative bacteria (GNB). Objectives: To review and meta-analyse the evidence for using commercially available molecular tests for the direct detection of AMR determinants in GNB-positive blood cultures (PBCs). Data sources: PubMed, Scopus and ISI Web of Knowledge. Study eligibility criteria: Clinical studies evaluating the performance of two major commercial systems, namely the Verigene® and FilmArray® systems, for rapid testing of GNB-PBCs, in comparison with the phenotypic or genotypic methods performed on GNB-PBC isolates. Methods: Literature search according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses criteria and, for meta-analysis of sensitivity and specificity of both systems, bivariate random-effects model. Results: Twenty studies were identified (3310 isolates) from 2006 to 2019. Nine studies were conducted in East Asia. In 15 studies using phenotypic comparators (1930 isolates), 1014 (52.5%) isolates were Escherichia coli, and 287 (14.9%) of all the isolates displayed AMR phenotypes. In five studies using genotypic comparators (1380 isolates), 585 (42.4%) were E. coli, and 100 (7.2%) of all the isolates displayed AMR genotypes. Pooled sensitivity and specificity estimates for detection of AMR determinants by the Verigene (i.e. CTX-M, IMP, KPC, NDM, OXA and VIM) and/or FilmArray (i.e. KPC) systems were 85.3% (95% CI 79.9%–89.4%) and 99.1% (95% CI 98.2%–99.5%), respectively, across the 15 studies, and 95.5% (95% CI 89.2%–98.2%) and 99.7% (95% CI 99.1%–99.9%), respectively, across the five studies. Conclusions: Our findings show that the Verigene and FilmArray systems may be a valid adjunct to the conventional microbiology (phenotypic or genotypic) methods used to identify AMR in GNBs. The FilmArray system detects only one AMR genotype, namely KPC, limiting its use. Both Verigene and FilmArray systems can miss important cephalosporin/carbapenem resistance phenotypes in a minority of cases. However, the sensitivity and specificity of both systems render them valuable clinical tools in timely identification of resistant isolates. Further studies will establish the prominence of such rapid diagnostics as standard of care in individuals with bloodstream infections.